Prevalence and Path Analysis on the Effects of Diarrhea and Life Course Determinants on Stunting in Children Under Two Years of Age in Kupang, East Nusa Tenggara - Ilma, Nabilah Nurul; Salimo, Harsono; Pamungkasari, Eti Poncorini (Journal of Maternal and Child Health, 2019)
Background: The interaction between infections and malnutrition has been recognized as a vicious cycle. Repeated diarrhoeal illnesses as well as other common childhood infections progressively altered the normal growth trajectories of children. This study aimed to analyze the effects of diarrhea and lifelong determinants on the incidence of stunting in children under two years in Kupang.Subjects and Method: This was a case-control study conducted in 25 integrated health posts in Alak and Oebobo Subdistricts, in Kupang, East Nusa Tenggara, from November December 2018. A sample of 200 children under two years was selected by multi-stage random sampling. The dependent variable was stunting. The independent variables were diarrhea, birth length, parental income, maternal education, exclusive breastfeeding, maternal height, maternal mid-upper arm circumference (MUAC), complementary feeding, maternal hygiene practice, and sanitation. The data were collected by questionnaire and analyzed by path analysis.Results: Stunting prevalence in Kupang was 30.5%. The risk of stunting was directly decreased by appropriate complementary feeding (b= -1.97; 95% CI= -3.55 to -0.39; p= 0.014), good hygiene practice (b= -4.38; 95% CI= - 6.63 to -2.12; p<0.001), good sanitation (b= -2.32; 95% CI= -4.00 to -0.64; p= 0.007), and birth length ≥48 cm (b= -2.22; 95% CI= -3.74 to -0.69; p= 0.004). The risk of stunting was directly increased by diarrhea (b= 2.55; 95% CI= 1.01 to 4.09; p= 0.001). It was indirectly affected by parental income, maternal education, exclusive breastfeeding, maternal height, and maternal MUAC at pregnancy.Conclusion: The risk of stunting is directly decreased by appropriate complementary feeding, good hygiene practice, good sanitation, and birth length ≥48 cm. The risk of stunting is directly increased by diarrhea. It is indirectly affected by parental income, maternal education, exclusive breastfeeding, maternal height, and maternal MUAC at pregnancy.Keywords: stunting, determinants, prevalence, diarrheaCorrespondence: Nabilah Nurul Ilma. Masters Program in Public Health. Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: nabilahnurul86@gmail.com. Mobile: +6287838555468.Journal of Maternal and Child Health, 2019, 4(4): 230-241https://doi.org/10.26911/thejmch.2019.04.04.02